Indigenous farmers’ perception of climate vulnerability, barriers and factors influencing farmers adaptation intention: evidence from mountainous area of Vietnam - Manh, Nguyen The; Ahmad, Mokbul Morshed; Pal, Indrajit; Nguyen, Thi Phuoc Lai (Frontiers in Sustainable Food Systems, 2023)
Climate change has adversely affected the agriculture of indigenous farmers. Farmers can lessen agricultural losses by using adaptation strategies to climate change. However, the adaptation process depends on several factors, including barriers. This paper examines the farmers’ opinion toward adaptation barriers and tries to identify how the barriers influence farmers’ adaptation intention. We collected data from 362 randomly selected farmers by using face to face interview method and focus group discussions in Backan province, Vietnam. The severity index technique was applied to calculate farmers’ perception of barriers and climate change vulnerability indexes, and we used the probit model to determine the factors affecting farmers’ adaptation intention. The results indicate that farmers identified ten internal factors and fourteen external barrier factors that influence the adaptation intention. Moreover, probit model confirmed that farmers’ adaptation intention was significantly affected by education level, major occupation, income, lack of technical process, high cost of farm labor, lack of access to pesticides, and lack of technical officers. As a result, climate vulnerability indexes and barriers, and adaptation factors should be considered for designing and performing the policies in the future for indigenous farmers.